PERBEDAAN NILAI MCV DAN MCHC PADA PASIEN KANKER OVARIUM DENGAN DAN TANPA KEMOTERAPI DI RSUD ULIN BANJARMASIN - Putri, Ajeng Alifia; Yuseran, Hariadi; Aflanie, Iwan (Homeostasis, 2023)
The ovary is one of the female reproductive organs which is where the egg or ovum is produced. Ovarian cancer is a gynecological malignancy that can arise from disorders of the ovarian epithelial cells. The treatment that is often used to treat ovarian cancer is chemotherapy. Chemotherapy can improve the clinical condition of ovarian cancer patients. Erythrocyte indices like Mean Corpuscular Volume (MCV) and Mean Corpuscular Hemoglobin Concentration (MCHC) can be used to examine anemia and chemotherapy. Between January and December 2021, the aim of this study was to compare the MCV and MCHC values of ovarian cancer patients receiving and not receiving chemotherapy at Ulin Banjarmasin General Hospital. An analytical observational study with a crosssectional design was used for the research design. According to the findings of the study, only 54 of the 110 study participants met the inclusion criteria at Ulin Hospital, Banjarmasin's medical record installation. The unpaired t-test was used for the analysis.  The results showed that the mean MCV values with and without chemotherapy were 86,8±3,8 fl and 81,4±7,5 fl (p<0,05), and the mean MCHC values without chemotherapy were 32,5±1,2 g/dl and 31,6±1,3 g/dl (p<0,05). It can be concluded that there are differences in MCV and MCHC values in ovarian cancer patients with and without chemotherapy.